2019
DOI: 10.1002/ca.23391
|View full text |Cite
|
Sign up to set email alerts
|

Active contractile properties of fascia

Abstract: The ubiquitous network of fascial tissues in the human body is usually regarded as a passive contributor to musculoskeletal dynamics. This review aims to highlight the current understanding of fascial stiffness regulation. Notably the ability for active cellular contraction which may augment the stiffness of fascial tissues and thereby contribute to musculoskeletal dynamics. A related narrative literature search via PubMed and Google Scholar reveals a multitude of studies indicating that the intrafascial prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…An increase in FT elasticity, a major positive outcome observed in this study, is liable to bring about muscle strengthening, which is needed to increase control over the body in terms of functions such as physical performance (Barassi et al, 2019). According to Klingler et al, increased fascial stiffness has been reported in ulnar nerve compression syndrome and in myofascial neck pain (Schleip and Klingler, 2019). If responses to SI therapy result in a reduction of tissue stiffness in dominant upper limb, as found in this study, it can be hypothesized that the therapy could lead to a reduction in pain and restoration of lost functions in patients with muscular disorders.…”
Section: Discussionmentioning
confidence: 58%
“…An increase in FT elasticity, a major positive outcome observed in this study, is liable to bring about muscle strengthening, which is needed to increase control over the body in terms of functions such as physical performance (Barassi et al, 2019). According to Klingler et al, increased fascial stiffness has been reported in ulnar nerve compression syndrome and in myofascial neck pain (Schleip and Klingler, 2019). If responses to SI therapy result in a reduction of tissue stiffness in dominant upper limb, as found in this study, it can be hypothesized that the therapy could lead to a reduction in pain and restoration of lost functions in patients with muscular disorders.…”
Section: Discussionmentioning
confidence: 58%
“…This would then make the stress/strain ratio used in most biomechanical research -Young's Modulus -virtually meaningless because it will be different at each point along the non-linear curve. In addition, the origin of the curve never reaches zero stress because of the intrinsic tension contained within the system (Masi and Hannon, 2009;Schleip and Klingler, 2019). It should be pointed out that the dynamics of tensegrity structures are quite similar to living tissues in that they also behave non-linearly and are incredibly complicated to analyze mathematically (Caluwaerts et al 2014) etc; and there is another important point to make.…”
Section: The Age-old Problemmentioning
confidence: 99%
“…We also have the deep fascia that involves muscle groups organizing the synchronism of the movement at a distance. It has the ability to transmit strength and save energy [12].…”
Section: Muscles and Fasciae Of Movementmentioning
confidence: 99%
“…The transverse septum will give rise to the phrenic center or tendon center of the diaphragm. The phrenic nerve innervates the afferent and efferent part of this structure [9][10][11][12][13][14][15]. The posterior part of the diaphragmatic dome develops from the mesenchymal cells derived from the pleural mesoderm.…”
Section: Diaphragm Formationmentioning
confidence: 99%